The Influence of the Use of Student Worksheet Problem-Based to Increase Problem Solving Skills and Learning Outcomes - Evendi Evendi; A. Halim; Yusrizal Yusrizal; Elisa Elisa; Oka Melawati (Postgraduate, University of Mataram, 2022)
Problem-solving skills are the needs of students in the 21st century so they are deemed necessary to have. One of the 2013 curriculum imposed by the government focuses students on problem-solving skills. The purpose of this study was to identify the influence of using problem-based Student worksheets on improving problem-solving skills and student learning outcomes on business and energy materials. This study uses a quantitative approach with a quasi-experimental research design. student worksheet implementation design uses One Group Pretest-Posttest Design. The instruments used in this study were problem-based students’ worksheets, problem-solving skills tests, and learning outcomes tests. The problem-solving skills of students were analyzed using the N-Gain test to see the effect before and after the problem-based student worksheet was implemented. The results of the student worksheet feasibility test obtained a percentage of 98.30% indicating that the student worksheet problem-based to improve problem-solving skills and learning outcomes is very feasible to use. The results of the implementation of problem-based student worksheets can improve students' problem-solving skills which are marked by an increase in the pretest-posttest value based on the results of the experimental class N-gain test of 0.93 in the high category, the control class N-gain value of 0.60 in the medium category. The learning outcomes test showed an increase in the N-gain value for the experimental class by 0.71 in the high category, the N-gain value for the control class by 0.50 in the medium category